2019
DOI: 10.13102/sociobiology.v66i2.3554
|View full text |Cite
|
Sign up to set email alerts
|

Dear Enemy Phenomenon in the Ant Ectatomma brunneum (Formicidae: Ectatomminae): Chemical Signals Mediate Intraspecific Agressive Interactions

Abstract: The integrity of ant colonies depends exclusively on social relationships between their individuals, especially the ability of communication between group members, which is mainly mediated through chemical signals. Another important feature of ant behavior is territory defense, since they need to gather large amounts of food to feed their larvae, males and breeding females. Thereby, ants might display behavioral strategies to defend their territories from intruders. Here we investigated whether Ectatomma brunn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…In normal conditions, under the influence of the geomagnetic field, we found higher levels of aggression among E. brunneum ants (scores for before in Fig 3A ) whose nests were further apart in more than 100 m (Fig 2). This finding means that these ants are tolerant to individuals from nests in a radius of 100 m. Pereira et al (2019) showed that E. brunneum colonies are more tolerant to ants from nearest the nanoparticles are mainly in the superparamagnetic state, and in the head, the nanoparticles are mainly single domains and superparamagnetic nanoparticles in the blocked state. Magnetometry studies done in other ants have shown that all parts of the ant body are magnetic (Wajnberg et al, 2010), but the abdomen and the head show different magnetic properties.…”
Section: Discussionmentioning
confidence: 88%
“…In normal conditions, under the influence of the geomagnetic field, we found higher levels of aggression among E. brunneum ants (scores for before in Fig 3A ) whose nests were further apart in more than 100 m (Fig 2). This finding means that these ants are tolerant to individuals from nests in a radius of 100 m. Pereira et al (2019) showed that E. brunneum colonies are more tolerant to ants from nearest the nanoparticles are mainly in the superparamagnetic state, and in the head, the nanoparticles are mainly single domains and superparamagnetic nanoparticles in the blocked state. Magnetometry studies done in other ants have shown that all parts of the ant body are magnetic (Wajnberg et al, 2010), but the abdomen and the head show different magnetic properties.…”
Section: Discussionmentioning
confidence: 88%
“…brunneum (Pereira et al, 2019). Dodecano presente apenas em P. clavata é relatado pela primeira vez em formigas, sendo encontrado em extratos da casca de planta medicinal nativa da Ásia Symplocos crataegoides (Govindarajan et al 2016).…”
Section: Volatilômicaunclassified